2008
DOI: 10.1080/09585190802051410
|View full text |Cite
|
Sign up to set email alerts
|

Emotion work in the Hellenic frontline services environment: how it relates to emotional exhaustion and work attitudes

Abstract: Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 61 publications
(84 reference statements)
2
41
0
4
Order By: Relevance
“…Bozionelos and Kiamouthe (2008) suggest that though emotional exhaustion has been theoretically considered as an outcome of emotion work after review, they found that limited empirical evidence concurs with this view. Logically, therefore, Bozionelos and Kiamouthe (2008) suggest that emotion work should relate to work attitudes.…”
Section: Work Attitudementioning
confidence: 77%
See 2 more Smart Citations
“…Bozionelos and Kiamouthe (2008) suggest that though emotional exhaustion has been theoretically considered as an outcome of emotion work after review, they found that limited empirical evidence concurs with this view. Logically, therefore, Bozionelos and Kiamouthe (2008) suggest that emotion work should relate to work attitudes.…”
Section: Work Attitudementioning
confidence: 77%
“…Surface acting involves the suppression of felt emotions combined with the adoption of an emotional mask; which is a process that imposes substantial strain, and is potentially psychologically and physically draining. In particular, Bozionelos and Kiamouthe (2008) indicated that frequent engagement in surface acting, that is the regular disguise of felt emotions, was especially emotionally taxing and is is detrimental to employees" well-being (Brotheridge and Grandey 2002). Surface acting has been considered as primary dimensions of emotion work, while frequency, intensity and variety have been considered as secondary dimensions, described as "emotion-related role requirements" (Brotheridge and Lee 2003).…”
Section: Surface Acting Emotion Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Az érzelmi munka és a kiégés között található összefüggést több kutatás vizsgálta, melyek szerint az érzelmi munka önmagában képes bejósolni a kiégés valamennyi komponensét (Bozionelos & Kiamou, 2008;Le Blanc, Bakker, Peeters, van Heesch, & Schaufeli, 2001;Martínez-Iñigo, Totterdell, Alcover & Holman, 2007;Zapf és mtsai, 2001). Zapf szerint a kiégés arra utal, hogy a dolgozó nem képes többé menedzselni az érzelmeit annak érdekében, hogy betartsa az érzelemkifejezéssel kapcsolatos munkahelyi elôírásokat, követelményeket (Zapf, 2002).…”
Section: Bevezetésunclassified
“…Other scholars have noted that emotional labour itself is culturally specific (Das et al, 2008), and different cultures draw the line between genuine and artificial emotional performances very differently (e.g. Bozionelos and Kiamou, 2008). Culture is intimately tied to the way emotional labour is understood -not only in specifying emotion rules appropriate to different situations, but also in stipulating what counts as an emotion rule and what constitutes emotional hypocrisy.…”
Section: Social Constructionist and Psychoanalytic Approaches To Emotionmentioning
confidence: 99%